A 10‐year prospective study on single immediate implants. (2nd September 2020) - Seyssens, Lorenz; Eghbali, Aryan; Cosyn, Jan
Abstract: Aim: To evaluate the clinical, aesthetic and radiographical outcome of single immediate implant placement (IIP) after 10 years (a) and to identify putative risk factors for advanced mid‐facial recession (b). Material and Methods: Periodontally healthy patients with a thick gingival biotype and intact buccal bone wall were consecutively treated with a single immediate implant and crown in the aesthetic zone (15–25). Flapless surgery and socket grafting with deproteinized bovine bone mineral were performed. Seven patients received a connective tissue graft (CTG) at 3 months due to obvious alveolar process deficiency ( n  = 5) or advanced mid‐facial recession ( n  = 2). Clinical, aesthetic and radiographical outcomes at 10 years were compared to those at 5 years and CBCTs were taken at 10 years. Results: Twenty‐two patients (10 women; mean age 50) were consecutively treated and 18 could be re‐examined. Two implants failed and two patients died. None of the parameters differed between the 5‐ and 10‐year re‐assessment (marginal bone loss: 0.31 mm; plaque score: 15%; probing depth: 3.4 mm; bleeding on probing: 32%; pink aesthetic score: 10.61; mesial papillary recession: −0.03 mm; distal papillary recession: 0.22 mm; mid‐facial recession: 0.58 mm). Six implants (33%) demonstrated ≥1 mm mid‐facial recession. Putative risk factors were merely based on descriptive statistics and included buccal shoulder position, no CTG, convex emergence profile and central incisor position. Three implants (17%) had no visible buccal bone on CBCT. One of these was too buccally positioned, another yielded peri‐implant mucositis and another demonstrated peri‐implantitis. Conclusions: Advanced mid‐facial recession is common in the long term following IIP. Therefore, caution is required for IIP in the aesthetic zone.